Soviet historical science development in the second half of the 1980s: Challenges of Perestroika - O.V. Metel (Ученые записки Казанского университета: Серия Гуманитарные науки, 2021)
This article considers the development of Soviet historical science during the second half of the 1980s based on the analysis of periodicals, private sources, as well as clerical and other documents of Soviet universities and academic institutions. During the first stage, i.e., in 1985–1987, historians had to respond to the “challenge posed by the party” and turn to studying the topical problems of the recent past. However, the system of Soviet historical science was “stable” enough to cope with this “challenge” without profound transformations of the long-established mechanism of work among academic institutions and universities. The second stage of the Soviet historical science reorganization, i.e., in the second half of 1988–1990, was characterized by more radical changes that implied the institutional restructuring implemented within the framework of the program for the reorganization of the existing research centers and the “turn” to solving the urgent research problems. Additionally, a new space of public history, where publicists, writers, and historians discussed the “acute” problems of the recent past was developing with the very legitimacy of official Soviet historiography questioned.